A Model Proposal for Analyzing Open-Source Information in End-User Computers. Issue 3 (3rd July 2022) - Akarslan, Hüseyin
Abstract: Cloud, grid, parallel, volunteer, and opportunistic computing are different forms of distributed computing and each of these concepts addresses different problems in data analysis. One of the latest virtualization technologies, containerization, provides new capabilities with a thin layer on end-user desktop computers in the field of distributed computing. From the viewpoint of management information systems, the information is the key element in decisionmaking processes, and in the age of the Internet the information that is necessary for organizations is accessible from publicly available open sources. Every organization needs to operate an open-source intelligence process to use the open-source data in different levels of management. However, the problem is that each organization needs data scientists and hardware and software resources to fulfill this requirement. Big enterprise companies or governments can make an investment to solve this problem, but small and medium-sized enterprises or small institutions may not have enough budget. A distributed microservice-based data analysis model with the technology of Docker containerization on the end-user computers is proposed.